THESSALY UNDER THE SERBS (1348 - c. 1373) - Nikolić, Maja (Analecta Stagorum et Meteororum, 2022)
The rule of the Serbs in Thessaly began in 1348, when the military units of the Serbian Emperor Stefan Dušan, led by his prominent general Preljub, took over and incorporated it into the Serbian Empire. Preljub governed Thessaly until his death, in early 1356. After the short reign of Despot Nikephoros II Orsini (1356–1359), Thessaly was conquered by Dušan’s half-brother Symeon Uroš Palaiologos (1359–c. 1371), who proclaimed himself emperor. He was succeeded by his elder son, John Doukas Uroš Palaiologos, who ruled for a very short time (c. 1371/2–c. 1373), before retiring to Meteora as monk Joasaph, where he lived until his death in 1423, essentially becoming the second ktetor of Meteora. The rule of John Uroš was followed by that of Kaisar (Caesar) Alexios Angelos Philanthropenos, which marked the end of Thessaly’s Serbian period, lasting less than three decades.